Government Preference and the Optimal Choice of R&D Subsidy Policy: Innovation Subsidy or Product Subsidy? - Yongcong Yang (Journal of Applied Mathematics)
Taking government preference into consideration, we consider a three-stage game model to compare the differences of innovation subsidy and product subsidy. The findings reveal that stronger preference to consumers’ welfare leads to higher subsidy rates, which benefit not only consumers but also firms. To choose between the two subsidies, the optimal choice varies with the changing preference of policymakers. According to the results of numerical simulation, product subsidy is better than innovation subsidy in most cases, while the government’s expenditure of the former one is larger than the latter one. Moreover, subsidizing firms symmetrically and asymmetrically has different effects on the consequences.